Bagaimana Mengatasi Masalah Server-Lag pada Website Kampus Ketika Penyusunan KRS - Dimesa, Muhammad Khadlel Risanda; Syarif, Salman; Lubis, Reza Alwinata (Lembaga Yasin AlSys, 2023)
The purpose of this research is to analyze server-LAG problems on campus websites when preparing KRS. This type of research is qualitative research using experimental methods. Data collection techniques in this study used literature and interview methods. The literature method is a method used to obtain data and supporting theories in making web servers. Based on the results of the tests and analysis carried out, it can be concluded that the steps taken to overcome server lag on the campus website have been successful. Implementation of database optimization, caching and load balancing significantly improves server performance and reduces lag. This success in addressing the server lag issue helped create a better user experience during the KRS build period.